Prospek Pengembangan Usaha Handline Tuna di Perairan D.I. Yogyakarta: Tinjauan Sumber Daya dan Investasi - Mustaruddin Mustaruddin; Bambang Murdiyanto; Eko Sri Wiyono; Jufri Pachri Laitupa (Jurnal Ilmu Pertanian Indonesia, 2021)
In 2018, tuna production in D.I. Yogyakarta reached 371.66 tons, of which 75-82% were captured using the handline. The dominance of the tuna caught has led to the development of the handline that highly dependent on the potential of tuna resources. Investment prospects are also important because they become a reference for investors in investing in the tuna handline busineses. This study aims to analyze the potential of tuna fish resources including the spread of its fishing ground and analyze the feasibility of developing tuna handline buseneses in the waters of D.I. Yogyakarta. The data of this study were analyzed using the Schaefer model, mapping using geographic information system (GIS), and investment feasibility analysis. The potential of tuna fish production in the waters of D.I. Yogyakarta reached 628,53 tons/year, while the average production was 427,32 tons/year, so it is still prospective to be developed. Potential fishing ground for tuna handline was spreaded in the waters of Bantul Regency until the western border waters of Gunung Kidul Regency, and in the eastern waters of Gunung Kidul Regency. The tuna handline was also prospective to be developed its investment in D.I. Yogyakarta. The value of NPV, IRR, ROI, and B/C ratio of tuna handline were very good, i.e., IDR 425,121,064; 36.49%; 9,36; and 1.22 respectively. Keywords: fish resource, geographic information system, investment, the waters of D.I. Yogyakarta, tuna handline